Impact of bariatric surgery in elderly patients with obesity - PEREIRA,ADRIANO F. (2022)
ABSTRACT Introduction: to evaluate the long-term impact of bariatric surgery in the elderly population. Methods: a retrospective study including all patients older than 60 years who underwent Roux-en-Y gastric bypass (RYGB) at our center and maintained a follow-up longer than 1 year. Clinical and laboratory variables were studied to assess remission of obesity and its comorbidities, as well as variables directly related to the surgical procedure itself, including early and late complications. Results: fifty-six patients were studied, mostly female (76,8%), with a mean age of 64.02 ± 3.34. A rate of complications of 37,5% was observed, with 10,7% requiring hospital admission and emergency surgery. The mean excess weight loss (%EWL) was 74.22% ± 26.76. The remission rates of hypertension and diabetes mellitus were 26.08% and 54.54%, respectively. There was significant difference in BMI reduction (12.25 ± 5.42, p<0.001), total cholesterol (31.37 ± 38.89 p<0,001), LDL cholesterol (23.45 ± 34.9, p=0.002), HDL cholesterol (5.14 ± 11.13, p=0,024), triglycerides (48.85 ± 56.15 p<0.001), HbA1C (1,81 ± 1,97, p<0,001) e PCR (1.43 ± 1.96, p<0.001). Conclusion: bariatric surgery was effective in weight loss and remission of comorbidities in the elderly obese population within the long term.